ROLE OF REMITTANCE IN EMERGING AND DEVELOPING (EDC) ECONOMIES - Nur Shafiena, Sidik; Mohd Hasan, T.; Dyg Affizzah, A.M. (Kaizentrenovation Sdn Bhd, 2020)
This paper investigated the relationship between remittance and economic growth in selected countries in Asia using panel data analysis. The remittance becomes one of the major macro-economic factors which is highly significant to promote the long-run economic growth. The findings conclude that remittance is one of beneficial factor of economic growth. Nonetheless, the effects on the gross fixed capital formation are positive and statically significant. GDP indicates positive significant relationship in both fixed and random effect, at the same time we found a positive and significant relationship in the long run by utilizing FMOLS and DOLS model.